A comparative morphometric analysis of trained young male and female swimmers and table tennis players - Nandy, P.; Chatterjee, P.; Bandyopadhyay, A. (American Journal of Sports Science, 2016)
The study was designed to evaluate and compare the somatotype characteristics of male junior Swimmers, female junior Swimmers, and Table Tennis players. Twenty-six Swimmers and twenty-nine Table Tennis players were evaluated for their anthropometric and somatotype characteristics. Endomorphy, Mesomorphy and Ectomorphy components were evaluated for the entire groups. Mesomorphy components of male and female Swimmers were higher than the Table Tennis players. Total fat content was significantly higher in both male and female Table Tennis players when compared to the Swimmers. The male and female Swimmers and Table Tennis players were more endomorphic in average. Moreover, desired sports specific body type were not found when evaluated individually. The mesomorphy components were found to be higher in male Swimmers (30%) compared to 0% in female Table Tennis players.